The threads that tie protein-folding diseases - Jeffrey L. Brodsky (The Company of Biologists, 2014)
From unicellular organisms to humans, cells have evolved elegant systems to facilitate careful folding of proteins and the maintenance of protein homeostasis. Key modulators of protein homeostasis include a large, conserved family of proteins known as molecular chaperones, which augment the folding of nascent polypeptides and temper adverse consequences of cellular stress. However, errors in protein folding can still occur, resulting in the accumulation of misfolded proteins that strain cellular quality-control systems. In some cases, misfolded proteins can be targeted for degradation by the proteasome or via autophagy. Nevertheless, protein misfolding is a feature of many complex, genetically and clinically pleiotropic diseases, including neurodegenerative disorders and cancer. In recent years, substantial progress has been made in unraveling the complexity of protein folding using model systems, and we are now closer to being able to diagnose and treat the growing number of protein-folding diseases. To showcase some of these important recent advances, and also to inspire discussion on approaches to tackle unanswered questions, Disease Models & Mechanisms (DMM) presents a special collection of reviews from researchers at the cutting-edge of the field.